Об одной стохастической модели, приводящей к устойчивому распределению - Синайский, Е.С. (Український математичний журнал, 1997)
Інтегральне рівняння, що описує явище післядії, зокрема рівняння стану спадковопружного тіла, інтерпретується як стохастичпа модель з щільністю ймовірності випадкового часу запізнювання у вигляді експоненти дробового порядку Работиова. Вивчається наближення розподілу для сум величин з даною щільністю до стійкого закону розподілу. Встановлюються основні характеристики відповідного процесу відновлення. We consider an integral equation describing the contagion phenomenon, in particular, the equation of the state of a hereditarily elastic body, and interpret this equation as a stochastic model in which the Rabotnov exponent of fractional order plays the role of density of probability of random delay time. We invesgigate the approximation of the distribution for sums of values with a given density to the stable distribution law and establish the principal characteristics of the corresponding renewal process.